Educating in antimicrobial resistance awareness: adaptation of the Small World Initiative program to service-learning. Issue 17 (30th June 2018) - Valderrama, María José; González-Zorn, Bruno; de Pablo, Pilar Calvo; Díez-Orejas, Rosalía; Fernández-Acero, Teresa; Gil-Serna, Jessica; de Juan, Lucía; Martín, Humberto; Molina, María; Navarro-García, Federico; Patiño, Belén; Pla, Jesús; et al.
Abstract: The Small World Initiative (SWI) and Tiny Earth are a consolidated and successful education programs rooted in the USA that tackle the antibiotic crisis by a crowdsourcing strategy. Based on active learning, it challenges young students to discover novel bioactive-producing microorganisms from environmental soil samples. Besides its pedagogical efficiency to impart microbiology content in academic curricula, SWI promotes vocations in research and development in Experimental Sciences and, at the same time, disseminates the antibiotic awareness guidelines of the World Health Organization. We have adapted the SWI program to the Spanish academic environment by a pioneering hierarchic strategy based on service-learning that involves two education levels (higher education and high school) with different degrees of responsibility. Throughout the academic year, 23 SWI teams, each consisting of 3–7 undergraduate students led by one faculty member, coordinated off-campus programs in 22 local high schools, involving 597 high school students as researchers. Post-survey-based evaluation of the program reveals a satisfactory achievement of goals: acquiring scientific abilities and general or personal competences by university students, as well as promoting academic decisions to inspire vocations for science- and technology-oriented degrees in younger students, and successfully communicating scientific culture in antimicrobial resistance to a young stratum of society. Abstract : Adaptation of the Small World Initiative crowdsourcing program for antibiotic awareness and discovery to a service-learning pedagogic strategy by integrating university and pre-university delivery.